2008
DOI: 10.1179/030192307x239588
|View full text |Cite
|
Sign up to set email alerts
|

Influence of operational parameters on silicon in hot metal from Corex

Abstract: Quality steel production at low cost demands superior quality of hot metal (HM) with low silicon (Si) and sulphur. High silicon is undesirable for its subsequent treatment during steelmaking, making the process costlier and less productive, hence there have been constant efforts to lower the silicon content in HM. Corex is the only commercially established and proven smelting reduction ironmaking technology alterative to conventional blast furnace (BF) ironmaking. While the mechanism of silicon transfer is lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 12 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…On the other hand, the nitride may be formed on the surface of tuyere under the condition of the high gas temperature, and it could act as a thermal insulating protective film [25]. The production practices of India Jindal [26] and China Baosteel [20] show that when the volume fraction of additional N 2 injection is 8% or more, the number of damaged tuyere decreases effectively and the service life of tuyere is prolonged.…”
Section: Optimization Of Blast Systemmentioning
confidence: 99%
“…On the other hand, the nitride may be formed on the surface of tuyere under the condition of the high gas temperature, and it could act as a thermal insulating protective film [25]. The production practices of India Jindal [26] and China Baosteel [20] show that when the volume fraction of additional N 2 injection is 8% or more, the number of damaged tuyere decreases effectively and the service life of tuyere is prolonged.…”
Section: Optimization Of Blast Systemmentioning
confidence: 99%
“…Industrial applications have proved that the lump coal quality has a significant impact on stable operation and energy consumption. Kumar [3,4] et al revealed that the quality of lump coal could affect the fuel ratio and Si content in hot metal, and then proposed suitable quality requirements for lump coal used in the COREX process [5,6]. Guo et al found that the metallurgical properties of coal greatly influenced the temperature of hot metal [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The reduction process is accomplished by further reaction of SiO in the gas phase with the carbon dissolved in the trickling metal droplets passing through the region extending between the bosh and the hearth and gets transferred as silicon to the metal. The reduction of SiO2 to volatile SiO proceeds also by the action of C in the coke, CO or SiC [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%